Market Reaction To Earnings Announcement: The Role Of Non-Financial Information Disclosure - Rendy Harnadi; R. Muh. Syah Arief Atmaja Wijaya (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze market reactions to earnings announcements by examining the role of non-financial information disclosure, namely Carbon Emission Disclosure (CED) and Good Corporate Governance (GCG), in oil, gas, and coal subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Market reaction is proxied by abnormal return as a response to information published during earnings announcements. This study employs signalling theory and the efficient market hypothesis, which suggest that the market reacts to information considered relevant, whether financial or non-financial. Carbon emission disclosure reflects a company’s transparency regarding environmental issues, while GCG represents the quality of corporate governance. The research method used is an event study with a quantitative approach. Data were obtained from the annual reports and sustainability reports of oil, gas, and coal subsector companies listed on the IDX. The results are expected to demonstrate the influence of carbon emission disclosure and GCG in strengthening or weakening market reactions to earnings announcements. This study is expected to contribute to the capital market accounting literature regarding the role of non-financial information in investor decision-making.